Reasons for maternal near-miss in Bahir Dar city administration, northwest Ethiopia: a qualitative interview approach using socio-ecological model - Workineh, Yinager; Alene, Getu Degu; Fekadu, Gedefaw Abeje (Frontiers in Global Women's Health, 2025)
IntroductionMaternal near-miss means the experience of a woman who encounters complications of pregnancy, childbirth, or within 42 days of termination but survives. Maternal near-miss is common in developing nations like Ethiopia. Exploring healthcare system risk factors and opportunities informs policy, but understanding the complex contributors to maternal near-miss remains limited in the Ethiopian context. Therefore, this study aims to explore reasons using a socio-ecological model in Bahir Dar City, Ethiopia, 2023.MethodsA phenomenological study was conducted in the rural part of Bahir Dar city administration, northwest Ethiopia, from September 28th–December 10th, 2023. In-depth interviewees were women who experienced maternal near-miss. Key informants included husbands, women development army leaders, health extension workers, obstetric care providers, and health office holders. Participants were purposively selected until information saturation was reached, after interviewing twenty-five individuals. Data were collected using open-ended interview guides, with audio recordings and field notes. Verbatim transcription was conducted after each interview, and contextual translation was used to translate Amharic transcripts into English. Findings were made trustworthy through data triangulation, member checks, clear descriptions, and contextual translation. Data were analyzed using the framework analysis technique with Open Code 4.03, and results were reported within each theme.ResultsBased on the Socio-Ecological Model, risk factors, protective factors, and strategies emerged from in-depth and key informant interviews. Individual-level reasons included poor knowledge, trust in traditional practices, and lack of decision-making power. Family-level contributors included male dominance, negligence, and disagreement. Organizational-level reasons encompassed non-compassionate care, resource scarcity, consultation delays, and lack of privacy. Community-level contributors included rumors, conflicts, transportation barriers, and harmful cultural practices. Public policy-level reasons were a lack of cascading protocols or guidelines and lengthy referral bureaucracy. Protective factors against maternal near-miss were identified at various levels, including self-care, acceptance of instruction, adaptation to modern healthcare, family trust-relationship, exempted services, mentorship, a three-tier healthcare system, and enhanced community engagement.ConclusionMaternal near-miss was determined by complex contributors and opportunities at intrapersonal, interpersonal, organizational, community, and policy-level. We recommend addressing risk factors and utilizing potential opportunities to prevent maternal near-miss.